2017
DOI: 10.1016/j.beproc.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Further examination of the temporal stability of alcohol demand

Abstract: Demand, or the amount of a substance consumed as a function of price, is a central dependent measure in behavioral economic research and represents the relative valuation of a substance. Although demand is often utilized as an index of substance use severity and is assumed to be relatively stable, recent experimental and clinical research has identified conditions in which demand can be manipulated, such as through craving and stress inductions, and treatment. Our study examines the 1-month reliability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 56 publications
(99 reference statements)
7
33
2
Order By: Relevance
“…The APT results obtained from our U.S. sample are highly consistent with those obtained from university students at the current site and elsewhere in the United States (Acuff and Murphy, ; Berman and Martinetti, ; Gentile et al., ; MacKillop et al., ; Martinetti et al., ; Murphy and MacKillop, ; Yurasek et al., ). The APT reliably produces an inverse relationship between price and consumption, with binge‐level reported consumption at lower alcohol prices, such as $3.00 or less (Berman and Martinetti, ), and the current U.S. data reflect these results.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The APT results obtained from our U.S. sample are highly consistent with those obtained from university students at the current site and elsewhere in the United States (Acuff and Murphy, ; Berman and Martinetti, ; Gentile et al., ; MacKillop et al., ; Martinetti et al., ; Murphy and MacKillop, ; Yurasek et al., ). The APT reliably produces an inverse relationship between price and consumption, with binge‐level reported consumption at lower alcohol prices, such as $3.00 or less (Berman and Martinetti, ), and the current U.S. data reflect these results.…”
Section: Discussionsupporting
confidence: 86%
“…Murphy and colleagues () compared the APT with other instruments that have been shown to accurately measure alcohol consumption and found that the APT produced similar results, thus demonstrating good construct validity. High correlations between test and retest scores on the APT and derived demand indices have been well established (Acuff and Murphy, ; Murphy et al., ), and Amlung and colleagues () observed strong relationships between demand metrics assessed with the APT and those produced from actual alcohol purchases.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The alcohol purchase task (APT; Murphy & MacKillop, 2006) asks participants to report the number of alcoholic drinks they would purchase and consume at a party between 9:00 PM and 1:00 AM across 20 escalating price points. Although many indices can be calculated using the APT, the current study elected to focus on intensity, elasticity, and O max , as these have shown good reliability (Acuff and Murphy, 2017; Murphy et al, 2009) and the most robust associations with substance misuse (Murphy et al, 2009; Teeters and Murphy, 2015). Further, hypothetical purchase choices have been shown to correspond to actual choices made with real monetary amounts (Amlung et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…5 Importantly, alcohol demand has been found equivalent under real and hypothetical conditions, where participants do not consume substances purchased. 6 Accordingly, the use of a hypothetical APT has gained interest because of evidence of construct validity, 7 temporal stability 8 and higher efficiency 3 compared with more traditional operant choice procedures such as self-administration paradigms. More recently, there has been an interest in understanding the relative sensitivity of each demand indicator to detect substance-related outcomes and variables affecting them.…”
Section: Introductionmentioning
confidence: 99%